Microglia-Derived Brain Macrophages Associate with Glioblastoma Stem Cells: A Potential Mechanism for Tumor Progression Revealed by AI-Assisted Analysis - Yuqi Zheng; Haneya Fuse; Islam Alzoubi; Manuel B. Graeber (Cells)
Background: Malignant gliomas, and notably glioblastoma, are highly aggressive brain tumors. Understanding the mechanisms underlying their progression is crucial for developing more effective treatments. Recent studies have highlighted the role of microglia and brain macrophages in glioblastoma development, but the specific interactions between these immune cells and glioblastoma stem cells (GSCs) remain unclear. Methods: To address this question, we have utilized AI-assisted cell recognition to investigate the spatial relationship between GSCs expressing high levels of CD276 (B7-H3) and microglia- and bone marrow-derived brain macrophages, respectively. Results: Using PathoFusion, our previously developed open-source AI framework, we were able to map specific immunohistochemical phenotypes at the single-cell level within whole-slide images. This approach enabled us to selectively identify Iba1+ and CD163+ macrophages as well as CD276+ GSCs with high specificity and to study their co-localization. Our analysis suggests a closer association of Iba1+ macrophages with GSCs than between CD163+ macrophages and GSCs in glioblastoma. Conclusions: Our findings provide novel insights into the spatial context of tumor immunity in glioblastoma and point to microglia-GSC interactions as a potential mechanism for tumor progression, especially during diffuse tissue infiltration. These findings have significant implications for our understanding of glioblastoma biology, providing a foundation for a comprehensive analysis of microglia activation phenotypes during glioma development. This, in turn, may lead to new therapeutic strategies targeting the early stages of the immune microenvironment of glioblastoma.